2021
DOI: 10.1155/2021/6657595
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation and Flow Modification in the Anterior Cerebral Artery after Pipeline Embolization Device Deployment across the Internal Carotid Artery Terminus

Abstract: Background and Objective. Whether anterior cerebral artery occlusion occurs after pipeline embolization devices (PEDs) are implanted to treat posterior communicating artery aneurysm is controversial. The purposes of this study were to explore the effect of a PED covering A1 on patients’ clinical prognosis and to evaluate the factors related to vascular occlusion. Method. The clinical and imaging data of PEDs in the postmarket multicenter registry study (PLUS) in China were retrospectively analyzed, and patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…A total of 57 studies 9 65 , encompassing 4647 records, involved 3789 patients with IA who were treated using FDSs. These studies employed a nonrandomized comparative design; the selection process is shown in Figure S1 (Supplemental Digital Content 2, http://links.lww.com/JS9/B226 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 57 studies 9 65 , encompassing 4647 records, involved 3789 patients with IA who were treated using FDSs. These studies employed a nonrandomized comparative design; the selection process is shown in Figure S1 (Supplemental Digital Content 2, http://links.lww.com/JS9/B226 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among 50 studies 9 19 , 22 , 23 , 25 35 , 37 47 , 49 , 50 , 52 63 , 65 involving 3100 patients, the overall obliteration rate was 77.5% (95% CI: 74.0–80.9%; I 2 , 69.8%; Table S3, Supplemental Digital Content 2, http://links.lww.com/JS9/B226 , Figure S2, Supplemental Digital Content 2, http://links.lww.com/JS9/B226 ). Subgroup analyses indicated a high obliteration rate regardless of the specific branches covered by FDSs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations